2021
DOI: 10.3389/fpsyg.2021.716010
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and Its Relationship With Lisdexamfetamine Dimesylate Treatment in Binge Eating Disorder

Abstract: High trait impulsivity is thought to contribute to the sense of loss of control over eating and impulses to binge eat experienced by those with binge eating disorder (BED). Lisdexamfetamine dimesylate (LDX), a drug approved for treatment of moderate to severe BED, has been shown to decrease impulsive features of BED. However, the relationship between LDX-related reductions of binge eating (BE) episodes and impulsivity has not yet been explored. Forty-one adults aged 18–40years with moderate to severe BED compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
1
13
1
Order By: Relevance
“…Impulsivity has been correlated with substance use disorders and eating disorders (Alcaraz-Iborra and Cubero, 2015;Kessler et al, 2016), particularly in the initiation of addiction behaviors, and has been demonstrated to have genetic components that have been identified in human GWAS (Dawe and Loxton, 2004;Bevilacqua and Goldman, 2013;Salatino-Oliveira et al, 2015;Giorgi et al, 2019;Sanchez-Roige et al, 2022). More specifically, treatment for attention deficit hyperactivity disorder (Lisdexamfetaminedimesylate; Vyvanse), which is stated to improve impulse control, has been shown to decrease binge-like eating (McElroy et al, 2015;Guerdjikova et al, 2016;Griffiths et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impulsivity has been correlated with substance use disorders and eating disorders (Alcaraz-Iborra and Cubero, 2015;Kessler et al, 2016), particularly in the initiation of addiction behaviors, and has been demonstrated to have genetic components that have been identified in human GWAS (Dawe and Loxton, 2004;Bevilacqua and Goldman, 2013;Salatino-Oliveira et al, 2015;Giorgi et al, 2019;Sanchez-Roige et al, 2022). More specifically, treatment for attention deficit hyperactivity disorder (Lisdexamfetaminedimesylate; Vyvanse), which is stated to improve impulse control, has been shown to decrease binge-like eating (McElroy et al, 2015;Guerdjikova et al, 2016;Griffiths et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A preprint of a human genome-wide association study (GWAS) using data from the Million Veterans Program reported three risk loci near the HFE, MCHR2, and LRP11 genes influencing binge eating (Burstein et al, 2022), and further human genome-wide polygenic scores found genetic correlations in individuals with ''binge-type'' eating disorders and psychiatric disorders, like ADHD and depression (Hübel et al, 2021). There is only one FDA-approved drug for BED, namely, the amphetamine-like compound lisdexamfetamine (Griffiths et al, 2021). Improving our understanding of the genetic basis of BED will potentially aid in the development of new therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Robust evidence supports stimulants as an e cacious treatment for impulsivity in youth with ADHD [16]; however, studies have not explored the effect of stimulants on LOC-E in children. Relevantly though, there is evidence that stimulants improve symptoms of binge eating in adults, and also, that stimulants may mediate this effect by improving impulsivity [17,18,19]. Notably, the stimulant lisdexamfetamine (LDX) received regulatory approval for the treatment of moderate to severe BED in adults based on one 11-week Phase 2 dose-nding study and two identically designed 12-week Phase 3 dose optimization studies [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Robust evidence supports stimulants as an efficacious treatment for impulsivity in youth with ADHD [16]; however, studies have not explored the effect of stimulants on LOC-E in children. Relevantly though, there is evidence that stimulants improve symptoms of binge eating in adults, and also, that stimulants may mediate this effect by improving impulsivity [17][18][19]. Notably, the stimulant lisdexamfetamine (LDX) received regulatory approval for the treatment of moderate to severe BED in adults based on one 11-week Phase 2 dose-finding study and two identically designed 12-week Phase 3 dose optimization studies [19][20][21].…”
Section: Introductionmentioning
confidence: 99%